ECTOPARASITE SPECIES COMPOSITION AND SEASONAL DYNAMICS IN DOMESTIC FOWL IN THE KRASNODAR KRAI - Ch. K. Fomo; T. S. Katayeva (Ветеринария сегодня)
One of the topical veterinary problems is infestation of domesticated chickens with ectoparasites. Permanent and temporary ectoparasites are vectors and reservoirs of more than 100 poultry infectious disease agents; they cause outbreaks of contagious diseases, thus decreasing performance and increasing economic losses. The results of ectoparasite fauna study in domesticated chickens in private backyards of the Krasnodar Krai are given. The research was carried out in 2017–2018 in 600 chickens of diﬀerent breeds and ages in four settlements: Gorkhutor (250 chickens), Industrialny (150), Yuzhny (100) and Svyazist (100). The results of the analysis demonstrated that chickens were infested with the following ectoparasite species: shaft louse Menopon gallinae with the highest invasion extensity of 100% and average invasion intensity of 18.6 parasites; poultry red mite Dermanyssus gallinae (55.7%) with average invasion intensity of 12.5 parasites; two species of scaly leg mites – Knemidocoptes mutans (17.7%) with average invasion intensity of 39.4 parasites; and Knemidocoptes gallinae (17.7%) with average invasion intensity of 35 parasites. Seasonal dynamics of fowl infestation with ectoparasites showed that shaft louse Menopon gallinae was found in spring, summer and autumn on all farms. Mites Dermanyssus gallinae were found more often in spring with maximum invasion extensity of 74.4%. The prevalence of scaly leg mites Knemidocoptes mutans and Knemidocoptes gallinae was as high as 76%. The results of the tests indicate that infestation of domesticated chickens with diﬀerent species of ectoparasitres can be linked with bad hygiene practice and free access system, creating favourable and stable environment for them. That is why it is necessary to use scientifcally justifed control measures, involving modern insecticides and tools.